Characterization and Cytotoxicity of Pseudomonas Mediated Rhamnolipids Against Breast Cancer MDA-MB-231 Cell Line - Mishra, Neelam; Rana, Kavita; Seelam, Siva Deepthi; Kumar, Rakesh; Pandey, Vijyendra; Salimath, Bharathi P.; Agsar, Dayanand (Frontiers in Bioengineering and Biotechnology, 2021)
A biosurfactant producing bacterium was identified as Pseudomonas aeruginosa DNM50 based on molecular characterization (NCBI accession no. MK351591). Structural characterization using MALDI-TOF revealed the presence of twelve different congeners of rhamnolipid such as Rha-C8-C8:1, Rha-C10-C8:1, Rha-C10-C10, Rha-C10-C12:1, Rha-C16:1, Rha-C16, Rha-C17:1, Rha-Rha-C10:1-C10:1, Rha-Rha-C10-C12, Rha-Rha-C10-C8, Rha-Rha-C10-C8:1, Rha-Rha-C8-C8. The radical scavenging activity of rhamnolipid (DNM50RL) was determined by 2, 3- diphenyl -1- picrylhydrazyl (DPPH) assay which showed an IC50 value of 101.8 µg/mL. The cytotoxic activity was investigated against MDA-MB-231 breast cancer cell lines by MTT (4, 5-dimethylthiazol -2-yl- 2, 5- diphenyl tetrazolium bromide) assay which showed a very low IC50 of 0.05 µg/mL at 72 h of treatment. Further, its activity was confirmed by resazurin and trypan blue dye exclusion assay with IC50 values of 0.01 µg/mL and 0.64 µg/mL at 72 h of treatment respectively. Thus, the DNM50RL would play a vital role in the treatment of breast cancer targeting inhibition of p38MAPK.